Tindak Pidana Pencucian Uang Dan Modusnya Dalam Perspektif Hukum Bisnis (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The progress of science and technology today is an advancement of human civilization which has an impact on all aspects of life, including the development and increasing diversity of motives and forms of crime. Along with this progress, the business world is also used as a means of committing crimes by criminals, one of which is money laundering which takes advantage of technological advances and system advances in the business world, such as taking advantage of the sophistication and ease of banking transactions and other forms of business activities. . In direct proportion to this, various efforts have been made to prevent and narrow the space for money laundering perpetrators, especially by building a legal system in the business world that can eradicate this white collar crime, both nationally and internationally.